2013
DOI: 10.1155/2013/193205
|View full text |Cite
|
Sign up to set email alerts
|

Skin Disorders among Elder Patients in a Referral Center in Northern Iran (2011)

Abstract: Background. Geriatric health care has become a worldwide concern, but a few statistical studies were carried out about skin diseases in this age group. In this study, we set out to determine the frequency as well as the age and gender distribution of dermatological diseases in geriatric patients. Materials and Methods. In a cross-sectional study, all patients over 60 years who were accepted to department of dermatology in north of Iran participated in this study. Baseline information and clinical examination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 12 publications
10
50
5
Order By: Relevance
“…In addition, BCC is more common in men than in women [6]. Several studies have reported BCC prevalence ranging from 0.1% to 8.8% [12,14,18]. In our study, BCC prevalence was 2.1%, and it affected both genders in equal measure.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In addition, BCC is more common in men than in women [6]. Several studies have reported BCC prevalence ranging from 0.1% to 8.8% [12,14,18]. In our study, BCC prevalence was 2.1%, and it affected both genders in equal measure.…”
Section: Discussionsupporting
confidence: 51%
“…In a study performed in İzmir, Turkey, the prevalence of SCC was found to be 26.6% among skin cancers other than MM [7]. In a study by Darjani et al [14] the SCC prevalence was reported to be 3.8%. In addition, SCC was 2-3 times more common in men than in women [19].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Itch is one of the most common complaints among elderly patients in dermatology clinics worldwide, with a reported prevalence ranging from 7.3 to 37.5 % [8][9][10][11][12][13]. In a recent comprehensive study using a standardized itch questionnaire administered to geriatric outpatient and nursing home patients, the prevalence of chronic itch was reported to be 25 %, with high itch intensity [visual analogue scale (VAS) score 6 ± 2.1] [1].…”
Section: Epidemiologymentioning
confidence: 99%
“…Atrophic dermatitis has been found to be more prone for developing carcinoma. 6 It has been pointed out that every cutaneous scar which is subjected to continuous irritation has an increased potential for malignant degeneration. 7 Neuman et al 8 proposed that the traumatic displacement of a living epithelial tissue into the dermis may cause a foreign body response and lead to a deranged regenerative process, resulting in a carcinomatous change.…”
Section: Discussionmentioning
confidence: 99%